1989
DOI: 10.5006/1.3577856
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Electrolyte and Alloy Composition on the Pitting Behavior of Stainless Steel Alloys

Abstract: The influence of Mo, V, W in ferrochrome alloys and of SO4 , C104, Clin an aqueous electrolyte was investigated electrochemically. The effect of minor alloying elements was most pronounced in the active potential region, prior to passivation; Mo, V reduced pitting while W enhanced it. CIpromoted pitting whereas SO4 and CI04 were inhibitors. Removal of surface sulfate ions destroyed this inhibitive effect. Relationships were developed between Epjn Em,,, i,P and [anion] which enabled the prediction of [S0] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…3). The behaviour of 316 and the 324 steel in chloride solutions is in agreement with previous works by other authors [ 2,9,10]. Only S326 steel (containing 5.5% of silicon), as it was mentioned before, exhibits a high corrosion resistance (also pitting), in all the examined media.…”
Section: Electrochemical Polarization Measurementssupporting
confidence: 92%
“…3). The behaviour of 316 and the 324 steel in chloride solutions is in agreement with previous works by other authors [ 2,9,10]. Only S326 steel (containing 5.5% of silicon), as it was mentioned before, exhibits a high corrosion resistance (also pitting), in all the examined media.…”
Section: Electrochemical Polarization Measurementssupporting
confidence: 92%
“…From the plots of this figure it is evident that the value of b 2 increases gradually from (1-5) and then abruptly rises and remains high up to compound (10). After this the value of b 2 greatly decreases for compounds (11)(12)(13). From the plots of Fig.…”
Section: Resultsmentioning
confidence: 75%
“…In this case, it can be concluded that these low concentrations of chloride are not sufficient to destroy completely the passivating film formed on the metallic surface. Also, the pits formed are not completely active and may undergo repassivation [3][4][5][6][7][8][9][10][11][12][13][14][15]. At higher concentrations of chloride ions the pits formed are assumed to be of the limiting active type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3), the values of E pit are deduced for the different NaCl concentrations and listed in Table (2). The previous studies carried out on the pitting corrosion in NaCl media reveal that there is a straight line relationship between E pit and log − Cl C in the following form [8][9][10] E pit = a 1 …”
Section: Experimental Workmentioning
confidence: 99%